„De rerum natura“: Fortschreibungsmodi des Lehrgedichts in der deutschsprachigen Naturlyrik der Gegenwart - Lorella Bosco (Internationale Zeitschrift für Kulturkomparatistik)
This article will examine how and to what extent the ancient tradition of the didactic poem exerts an influence on contemporary German nature poetry. It will focus in particular on Raoul Schrott’s „Tropen“ and Marion Poschmann’s „Geliehene Landschaften“, which, while different from each other, both offer clues to possible lines of influence. Although there is a long tradition of didascalic  poems in the German literature of the Renaissance and of the Enlightenment, my point of reference will be the ancient didactic poem, as it was shaped by Lucretius in his “De rerum natura”, because of its masterful intertwining of knowledge and poetry and its wholly secular view of nature, creation, and evolution, as well as the fact that it stresses the idea that life is accidental. These are the aspects of ancient didactic poetry that I will investigate in the aforementioned German poets  and works, with particular attention to the relationship between the knowledge of nature and the language of poetry. Both Schrott and Poschmann openly use the  word ‚Lehrgedicht‘ [didactic poem] in order to define their poems, in which the didactic parts function as a knowledge of “nature after nature.” As a consequence, their poetry revolves around the impossibility of an all-encompassing explanation of the world and takes as its theme the rupture that divides human beings from nature in the modern age. Consciousness of the intrinsic constructedness of the way we experience nature is, on the other hand, a condition for both its aesthetic perception and scientific enquiry. At the center of both Schrott’s and Poschmann’s poetry collections, albeit in different ways and with different emphases, we thereby find an understanding of nature as a void that can only be approached (but never overcome) by means of language. Herein lies the main difference between these contemporary poets and the ancient tradition.